Analisis Gaya Bahasa Dalam Lirik Lagu “Palestina Tercinta” Karya Shoutul Harokah (Kajian Stilistika) - Riza Fauzan; Heri Isnaini (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The results of this paper examine the use of language styles in the lyrics of the song Palestine Beloved by Shoutul Harokah through stylistic studies. The language of this song's lyrics is an expression of the writer's emotions which is manifested in the form of song lyrics or words. The method used is a qualitative descriptive method. The qualitative descriptive method is research that uses a post-positivist philosophical basis. The aim of this research is to interpret or describe the use of language styles in the lyrics of the song Palestine Beloved. The results of the research that has been carried out show that the use of language styles in this song mostly uses personification language styles, apart from that there is also the use of anadiplosis and synecdoche language styles.